IMPAACT 2016: Operationalizing HIV Intervention Adaptations to Inform the Science and Outcomes of Implementation - Libous, Jennifer L.; Montañez, Nicole A.; Dow, Dorothy E.; Kapetanovic, Suad; Buckley, Janice; Kakhu, Tebogo Jacqueline; Kamthunzi, Portia; Maliwichi, Limbika A.; Vhembo, Tichaona; Chawana, Tariro Dianah; Nematadzira, Teacler; Donenberg, Geri R. (Frontiers in Reproductive Health, 2021)
INTRODUCTION: Uptake of evidence-based interventions for youth living with HIV (YLWH) in sub-Saharan Africa (SSA) is complex, and cultural differences necessitate local adaptations to enhance effective implementation. Few models exist to guide intervention tailoring, yet operationalizing strategies is critical to inform science and implementation outcomes, namely acceptability, appropriateness, feasibility, fidelity, and sustainability. This paper describes operationalizing the ADAPT-ITT framework applied to a manualized trauma-informed cognitive behavioral therapy (TI-CBT) intervention addressing mental and sexual health for YLWH in SSA in preparation for a randomized controlled trial (RCT). METHODS: Phase 1 of the RCT focused on operationalizing ADAPT-ITT steps 3-7 to tailor the intervention for use in eight sites across Botswana, Malawi, South Africa, and Zimbabwe. Well-defined processes were developed to supplement the general guidelines for each step to provide clear, consistent direction on how to prepare and conduct each step, including documenting, assessing, and determining adaptations, while maintaining intervention fidelity. The processes provided efficient standardized step-by-step progression designed for future replication. All sites participated in Phase 1 using the created tools and strategies to translate and present the TI-CBT to community stakeholders for feedback informing local adaptations. RESULTS: The research team developed and operationalized materials guiding adaptation. A translation review process verified local adaptability, maintained core concepts and revealed differing interpretations of words, idioms, and culturally acceptable activities. Strategically designed tools comprised of feedback and translation verification forms resulted in meticulous management of adaptations. Robust collaborations between investigators, research managers, site personnel, and topical experts maximized multidisciplinary expertise, resulting in 10-15 personnel per site facilitating, collecting, assessing, and integrating local feedback. Processes and tools operationalized in steps 3-7 effectively addressed implementation outcomes during community engagements (n=108), focus groups (n=5-8 YLWH and caregivers per group), and strategic training of youth leaders. DISCUSSION: This paper offers a novel generalizable approach using well-defined processes to guide intervention adaptation building on the ADAPT-ITT framework. The processes strengthen the science of implementation and provide much-needed specificity in adaptation steps to optimize and sustain real-world impact and help researchers and community stakeholders maximize existing infrastructure, culture, and resources to inform implementation strategies.